OCCUPATIONAL STRUCTURE AND STRUCTURAL CHANGE IN INDONESIA, 1880–2000. (13th February 2020) - Marks, Daan; Bierman, Winny; van Zanden, Jan Luiten
Abstract : Osamu Saito's pioneering research into the long‐term changes in occupational structure of Japan has inspired scholars to take a fresh look at structural change in other countries. This article offers a case study of Indonesia. We find a rather slow pace of structural transformation until the 1970s – the immediate post‐war period even saw a reversal of trends. After 1970, during a growth spurt, employment growth in manufacturing was not impressive, and services were an even more important source of employment. The role played by by‐employment is also analysed, demonstrating that in 1905 the economy was quite diversified.